2022
DOI: 10.1186/s13054-022-04059-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous IgM-enriched immunoglobulins in critical COVID-19: a multicentre propensity-weighted cohort study

Abstract: Background A profound inflammation-mediated lung injury with long-term acute respiratory distress and high mortality is one of the major complications of critical COVID-19. Immunoglobulin M (IgM)-enriched immunoglobulins seem especially capable of mitigating the inflicted inflammatory harm. However, the efficacy of intravenous IgM-enriched preparations in critically ill patients with COVID-19 is largely unclear. Methods In this retrospective multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…A larger randomized, controlled clinical trial in patients with severe COVID-19 treated with IgM/IgA-enriched Ig preparations showed a trend towards a reduced composite deterioration/mortality rate (p = 0.096) when treatment was started before invasive mechanical ventilation and before respiratory dysfunction and coagulopathy had progressed into advanced stages [143]. A similar benefit with IgM/IgAenriched Ig preparations was observed in other studies in COVID-19 patients with less advanced disease (Table 1, [144]) [144,145].…”
Section: Studies With Ivig In Scapsupporting
confidence: 52%
“…A larger randomized, controlled clinical trial in patients with severe COVID-19 treated with IgM/IgA-enriched Ig preparations showed a trend towards a reduced composite deterioration/mortality rate (p = 0.096) when treatment was started before invasive mechanical ventilation and before respiratory dysfunction and coagulopathy had progressed into advanced stages [143]. A similar benefit with IgM/IgAenriched Ig preparations was observed in other studies in COVID-19 patients with less advanced disease (Table 1, [144]) [144,145].…”
Section: Studies With Ivig In Scapsupporting
confidence: 52%
“…The immunomodulatory properties of the antibody molecules may be of greater importance in critically ill patients, as initial clinical data with an IgM-enriched preparation are encouraging [21]. We expect that further clinical trials will provide a better picture of the possibilities of treating COVID-19 with antibodies.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in galactosylation, fucosylation, and sialylation are now well-established factors which drive differential IgG function, ranging from inhibitory/anti-inflammatory to activating complement and promoting antibody-dependent cellular cytotoxicity [ 42 ]. Finally, in light of recent antibody-based therapy research which has been stimulated by SARS-CoV-2 and which has been met with some success [ 43 , 44 , 45 , 46 , 47 ], consideration should also be given to the development and testing of IgM-enriched IVIg preparations or the utilisation of hyperimmune IVIg to provide standardised and controlled antibody content from patients that have recovered from CDI who have anti-toxin neutralising antibodies in their plasma. It would also be of interest to investigate the role of combinatorial therapy to enhance the capability of IVIg.…”
Section: Discussionmentioning
confidence: 99%